(untitled) (Archives of Criminology, 2006)
Violence against women, especially in the context of family violence, casts a question whether it is a social or perhaps a family, private problem. The Police’s reaction to reported acts is currently a fundamental problem. Disregarded reports may cause further humiliating living under violence for wman, while a man becomes strengthened in his heartless and commanding role. In addition, a conviction appears in victims that the police is ineffective, unreliable; hence it is better to keep the affair ‘within the four walls at home’. What i sit like in Poland? Do women often report the violence practiced by their partners? Ae they satisfied with the Police reaction? The results gained in IVAWS survey in Poland make the content of this paper.